Indicadores de eficiência em propriedades de bovinocultura leiteira na região extremo oeste de Santa Catarina - Ramon, Jonas Marcelo (2021)
Few rural companies mind their management controls, due to the reduced number of practical and efficient control methods available and able to adapt to its reality. Thus, there is a need to analyze the feasibility and the main efficiency indicators of milk production. This research aims to develop and evaluate a practical and efficient management system. The research was made in fifteen rural properties characterized as family production units with predominant dairy activity, very typical milk production systems in the region. These properties are located in four cities covered by Regional Management of Epagri of São Miguel do Oeste, which are assisted by the Agricultural Research and Rural Extension Company of Santa Catarina, in the extreme west of Santa Catarina. During the research, spreadsheets were developed that included assets, expenses and income, dairy controls and milk indicators to obtain twenty-six efficiency indicators. After a monthly collection and compilation of data obtained in the 12-month period, between January and December of 2020, a comparative analysis of the data and definition of the efficiency indicators that are responsible for the results and obtaining the highest gross margin per hectare and per annum. In the annual percentage indicator of return on invested capital, the average return was 3.62% per year, with only three properties reaching the proposed goal of being above 6%; in relation to the operating cost per liter produced, the average cost was R$1.58 per liter and only six properties reached the goal, which was to get a cost of less than R$1.50, those with feed based on pastures; the indicator liters produced per month per kilogram of live weight of lactating cows, the average was 1.16 liters per kilo of weight, 12 properties were above the target of more than one liter produced per kilo; for the indicator liters produced per hectare and per year, the average was 13,903.88 liters produced, only five properties reached the proposed goal of more than 15,000 liters of milk per hectare and per year; and, in the indicator liters sold per person and per day, the average obtained was 213 liters per person, with only four properties reaching the goal, which is more than 300 liters per person. Dairy cattle have a positive annual gross margin in all properties analyzed, which denotes economic viability at least in the short term, but thanks to the low return on invested capital and low gross margin per hectare of the majority, the trend is decapitalization and economic unviability in the medium and long term, if the same condition persists. However, dairy activity is technically feasible, since it is possible to produce fodder all year around and obtain high animal production, provided that it increases the number of lactating cows per hectare per person, making dairy cattle one of the most competitive activities on the efficient use of soil, capital and labor, when the activity is well managed.